MANGROVE REFORESTATION IN GAMPONG LAMPAGEUSUB-DISTRICT PEUKAN BADA-ACEH BESAR: REFORESTASI MANGROVE DI GAMPONG LAMPAGEUKECAMATAN PEUKAN BADA - Juliawati; Novi Mailidarni; Jauhari; Ilya Puryani; Nyak Yusfa; Fauziah Aida Fitri (PT. ROCE WISDOM ACEH, 2025)
Mangroves are tropical trees that thrive in intolerable conditions of mostly salty wood, coastal waters, and endless tides. Thanks to their ability to store large amounts of carbon, mangroves are a key weapon in the fight against climate change but are under threat around the world. By protecting mangroves, we can help protect the future of our planet. Referring to data from the Central Bureau of Statistics, the area of mangrove ecosystems in Aceh reaches 3.63 million hectares or 20.37% of the world's total area. With this significant area, Indonesia has a great responsibility in preserving the global mangrove ecosystem. Therefore, World Mangrove Day is an important moment to reflect on the efforts that have been made and take concrete actions in maintaining and preserving mangrove forests which are an important part of Indonesia's natural wealth. Mangroves play a crucial role in coastal ecosystems, serving as natural fortresses that protect beaches from erosion and storms, absorb carbon dioxide from the atmosphere, and provide habitat for a variety of marine and bird species. Given the severe environmental damage that occurred in Lampageu village due to the tsunami disaster, the tsunami survivors wanted to reforest the mangroves so that they returned to their original state. This is because mangrove ecosystems have so many functions and benefits for the lives of local villagers.